Translating cerebellar Purkinje neuron physiology to progress in dominantly inherited ataxia. (March 2014) - Chopra, Ravi; Shakkottai, Vikram G
ABSTRACT:  The cerebellum is an important structure for accurate control and timing of movement, and Purkinje neurons in the cerebellar cortex are key players in cerebellar motor control. Cerebellar dysfunction can result in ataxia, a disorder characterized by postural instability, gait disturbances and motor incoordination. Cerebellar ataxia is a symptom of a number of conditions, and the emerging evidence that Purkinje neuron dysfunction, in particular, abnormal Purkinje neuron repetitive firing, is a major driver of motor dysfunction in a subset of dominantly inherited ataxias is dicussed. Abnormalities in Purkinje neuron excitability that are observed in mouse models of each of these disorders, and where appropriate describe studies linking particular ion channels to aberrant excitability are also discussed. Common mechanisms of dysfunction and speculate about potential therapeutic targets, suggesting that Purkinje neuron firing abnormalities are a novel target for improving motor dysfunction in patients with some forms of dominantly inherited ataxia are proposed.